2016
DOI: 10.1021/acs.orglett.6b00254
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III) Chloride Catalyzed Formation of 3,4-Dihydro-2H-pyrans from α-Alkylated 1,3-Dicarbonyls. Selective Synthesis of α- and β-Lapachone

Abstract: A mild, catalytic method for the synthesis of 3,4-dihydro-2H-pyrans is described. The FeCl3-catalyzed transformation of aryl- and alkyl β-diketones enables synthetic access to functionalized pyran core structures incorporated in many natural products and biologically active target structures. The method represents a mild alternative to currently available reaction protocols relying on stoichiometric reagents and harsh reaction conditions. This FeCl3-catalyzed transformation has enabled the selective synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Existing reports to access this structural motif often utilize Brønsted or Lewis acid catalyzed [4 + 2]-cycloaddition reactions of o -alkynyl­(oxo)-benzenes 5 with alkenes 6 , or isochromene acetals 8 with vinyl boronates 9 (Figure B) . We herein present a mild and efficient strategy for the synthesis of tetrahydronaphthalenes 4 which was inspired by mechanistic insights obtained during our previous studies toward the synthesis of 3,4-dihydro- 2H -pyrans 2 from aryl ketones 1 bearing α-carbonyl substituents . The corresponding α-arylated analogs of 1 exhibit divergent reactivity upon Brønsted or Lewis acid catalysis resulting in either the preferential formation of pyrans 3 or the exclusive formation of tetrahydronaphthalenes 4 depending on the choice of activation (Figure A).…”
mentioning
confidence: 99%
“…Existing reports to access this structural motif often utilize Brønsted or Lewis acid catalyzed [4 + 2]-cycloaddition reactions of o -alkynyl­(oxo)-benzenes 5 with alkenes 6 , or isochromene acetals 8 with vinyl boronates 9 (Figure B) . We herein present a mild and efficient strategy for the synthesis of tetrahydronaphthalenes 4 which was inspired by mechanistic insights obtained during our previous studies toward the synthesis of 3,4-dihydro- 2H -pyrans 2 from aryl ketones 1 bearing α-carbonyl substituents . The corresponding α-arylated analogs of 1 exhibit divergent reactivity upon Brønsted or Lewis acid catalysis resulting in either the preferential formation of pyrans 3 or the exclusive formation of tetrahydronaphthalenes 4 depending on the choice of activation (Figure A).…”
mentioning
confidence: 99%
“…They have unsaturated side chains with one more carbon than the COM δ,ϵ‐unsaturated ketone substrates in Scheme 3b. The γ,δ‐unsaturated ketone substrates in Scheme 3c can be considered one CH 2 truncated versions of the COM substrates [29] . The alkenyl and alkynyl [30] keto subtrates in Scheme 3d and e bear slightly different unsaturated side chains but can be considered synthetic equivalents of the ones in Scheme 3c.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, for instance, it can be observed that lapachones present interesting π‐conjugated chromophoric units; relatively simple changes in their electronic structures involve a colour change that can be used to monitor their reaction (Scheme 30). [15a] …”
Section: Photophysical Propertiesmentioning
confidence: 99%